Students perception towards the implementation of asynchronous video lectures and video-based instructions in experimental fluid mechanics course - Yaacob, Mohd Rusdy; Velte, Clara Marika (Joint Journal of Novel Carbon Resource Sciences & Green Asia Strategy, 2021)
Computer-based approaches have recently become a fully viable alternative to classical lectures as a consequence of the global pandemic. In the Experimental Fluid Mechanics course at the Technical University of Denmark, a blended approach of video-based lectures and instructions and experimental work has been adopted. Students' feedback on this implementation have been collected through a series of questionnaires. The evaluation results reveal that both videobased lectures and video-based instructions are beneficial and should be fully adopted for the rest of the experiments.